Student readiness for change: acceptance of ai-integrated creative software - Teddy Marius Soikun (Penerbit Universiti Malaysia Sabah, 2024)
This Paper investigates how ready are design students to use AI-integrated creative software in producing their artwork. The researcher used a quantitative method and Likert-scale questionnaires to assess student’s familiarity with AI tools, their willingness to adopt AI, and also the perceived benefits from AI to enhance creativity. It was found that design students have generally have neutral to positive attitude towards AI in art and design but facing limited practical experience, insufficient training, and concerns with its impact on the artistic authenticity. While the design students curious on AI’s potential, they still need the practical experience and confidence to fully accept the change. This paper also proposes that future research should include ongoing studies with diverse participants and assess AI training education to boost design student’s skills and assurance with AI in producing designs.